Tuning porosity in macroscopic monolithic metal-organic frameworks for exceptional natural gas storage - B. M. Connolly (Nature Portfolio, 2019)
While metal–organic frameworks exhibit record-breaking gas storage capacities, their typically powdered form hinders their industrial applicability. Here, the authors engineer UiO-66 into centimetre-sized monoliths with optimal pore-size distributions, achieving benchmark volumetric working capacities for both CH4 and CO2.